2015
DOI: 10.1103/physreva.92.032706
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for unnatural-parity contributions to electron-impact ionization of laser-aligned atoms

Abstract: Recent measurements have examined the electron-impact ionization of excited-state laser-aligned Mg atoms. In this work we show that the ionization cross section arising from the geometry where the aligned atom is perpendicular to the scattering plane directly probes the unnatural parity contributions to the ionization amplitude. The contributions from natural parity partial waves cancel exactly in this geometry. Our calculations resolve the discrepancy between the nonzero measured cross sections in this plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Also, when alignment of the quantization axis was perpendicular to the scattering plane, theory predicted zero cross section, while experiment did not [1]. In follow-up work, Armstrong et al [2] found that the non-zero cross section comes from unnatural parity contributions. However, no study of the partial wave contributions to the cross sections has been performed until now.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, when alignment of the quantization axis was perpendicular to the scattering plane, theory predicted zero cross section, while experiment did not [1]. In follow-up work, Armstrong et al [2] found that the non-zero cross section comes from unnatural parity contributions. However, no study of the partial wave contributions to the cross sections has been performed until now.…”
Section: Introductionmentioning
confidence: 98%
“…They also provide information about the structure of the target atoms, and represent a stringent test of current theoretical models. In most cases, the initial state orientation is determined [1][2][3][4], however, a recent study has examined a collision process in which the final state ion is oriented [5]. In the case of oriented targets in the initial state, most of the work has been focused on oriented molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their laser-excited P-states can then be aligned in different directions with respect to the collision frame (see figure 5), thereby producing a four-fold cross section (QDCS) that depends on the incident electron momentum k 0 , the scattered and ejected electron momenta (k 1 , k 2 ), and the alignment of the excited atom k B . Comparison of the measured QDCS to theoretical calculations can then be made [21][22][23][24].…”
Section: University Of Manchester United Kingdommentioning
confidence: 99%
“…The study of ionizing collisions involving oriented targets has become more prevalent in recent years with improvements in experimental technology and computational power [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%